Optimisation of the germination test protocol for viability monitoring of Chamaecytisus proliferus seeds in genebank collections - Olbana, Tamiru; Hay, F.R.; Negawo, Alemayehu T.; Muchugi, A.; Jones, Christopher S. (International Seed Testing Association, 2025)
Many forage species exhibit seed dormancy, which prevents germination and poses challenges for seed growers and analysts. Various methods have been developed to overcome dormancy in different forage species, but their effectiveness varies depending on the species and environmental conditions during seed development and storage. The seeds of Chamaecytisus proliferus exhibit dormancy due to a hard seed coat and lens covering the embryo. To overcome this dormancy, we evaluated physical, mechanical and chemical scarification methods. Among the treatments, excised embryos achieved the highest germination proportion (0.95). Hot water treatment for 15, 20 and 25 minutes effectively broke dormancy, resulting in proportions of 0.89, 0.92 and 0.89 germinated seeds, respectively. Treatment with 0.1 or 0.2% KNO3 also enhanced germination, whereas a 0.3% solution led to lower germination (0.73). Exposure to concentrated H2SO4 increased germination but caused a high proportion of dead seeds and abnormal seedlings. Similarly, mechanical scarification using a scalpel blade resulted in low germination (0.70) and a high proportion of seedling abnormalities (0.3). All pre-treatments reduced mean germination time, with excised embryos germinating fastest. In conclusion, excised embryos and hot water treatment (15‐25 minutes) effectively break dormancy and enhance germination in Chamaecytisus proliferus.